1999
DOI: 10.1111/j.1574-6968.1999.tb13541.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fluidity affects functions of Cdr1p, a multidrug ABC transporter ofCandida albicans

Abstract: Earlier, we have shown that the overexpression of an ABC transporter, CDR1, is involved in the emergence of multidrug resistance in Candida albicans. In this study, we checked its function in vivo by expressing it in different isogenic Saccharomyces cerevisiae erg mutants, which accumulated various intermediates of the ergosterol biosynthesis and thus altered the membrane fluidity. Functions like the accumulation of rhodamine 123, beta-estradiol, fluconazole and floppase activity associated with Cdr1p were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Since Cdr1p functioning is also susceptible to alterations in membrane fluidity (34), we investigated the differences in the asymmetrical distribution of phospholipids by labeling with fluorescamine and quantitated aminophosphopholipids translocated to the outer monolayer in these clinical isolates (Fig.5). Since entire phosphatidylserine is localized predominantly in the cytoplasmic leaflet of the lipid bilayer, therefore the dye could label only externalized phosphatidylethanolamine as small percentage of this aminophospholipid is also present in outer monolayer (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Cdr1p functioning is also susceptible to alterations in membrane fluidity (34), we investigated the differences in the asymmetrical distribution of phospholipids by labeling with fluorescamine and quantitated aminophosphopholipids translocated to the outer monolayer in these clinical isolates (Fig.5). Since entire phosphatidylserine is localized predominantly in the cytoplasmic leaflet of the lipid bilayer, therefore the dye could label only externalized phosphatidylethanolamine as small percentage of this aminophospholipid is also present in outer monolayer (8).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that the drug resistant ABC protein of mammalian cells (P-glycoprotein [P-gp]), MDR proteins of yeasts (Pdr5p and Yor1p in Saccharomyces cerevisiae and Cdr1p and Cdr2p in C. albicans) can translocate phospholipids between the two monolayers of the plasma membrane, while P-gp has been shown to participate in sterol homeostasis in mammalian cells (5,23,24). Additionally, these drug extrusion pumps are found to be particularly sensitive to the nature and the changes in the physical state of the surrounding lipids (9,17,34-36). The fact that the lipids could also play an important role in azole susceptibilities is becoming apparent from a host of recent studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the function of these pumps has been shown to depend on plasma membrane lipids. For example, when the CDR1 (Candida drug resistance) gene was expressed in S. cerevisiae mutants, which accumulated various intermediates of ergosterol biosynthesis and showed increased membrane fluidity, an increased susceptibility to fluconazole compared to the wild-type was observed [75]. This phenomenon suggests that either membrane fluidity or sterol composition affects the function of the CDR1p.…”
Section: Regulation Of Fungal Virulence By Plasma Membrane Lipidsmentioning
confidence: 99%
“…The action of azoles on fungi is mediated by depletion of ergosterol, which results in the alteration of membrane fluidity [60]. In S. cerevisiae , Sc Hsp12p is known to influence plasma membrane fluidity enhancing the stability of the cell membrane [61].…”
Section: Discussionmentioning
confidence: 99%